VITAMIN CONTENTS OF SOME Salvia L. TAXA GROWING IN TURKEY - Sari, Aysel; Kursat, Murat; Civelek, Semsettin; Emre, Irfan (Springer, 2009)
[Abstract Not Available]
Keywords: Fatty-Acid; Antioxidant Activities; Beta-Carotene; Seed Oils; Extracts; Capacity